Keterwakilan Perempuan di Parlemen: Komparasi Indonesia dan Korea Selatan - Ella Syafputri (Institute of International Studies, 2014)
The article examines the similarities and differences in terms of women representation in the parliaments of Indonesia and South Korea. With the methods of literature study, the author constructs the factors inhibiting women's involvement in politics in Indonesia and Korea as a member of the legislature. From 1996 to 2014, Indonesia has more women MPs ratio than Korea. Exceptions only occur in 2004, in which the ratio between women and men in Korea's national parliament surpassed Indonesia. In this article the author argues representation of women in parliament both in Indonesia and South Korea are very influenced by political culture and recruitment system by political party. Both countries apply a minimum quota of women as legislators, as one initiative helps bridging the gender ratio in parliament. However the two Asian countries have not yet succeeded in achieving these targets.